Mental Health Promotion Through Collection of Global Opinion Data - Seeman, Neil; G. Fogler, Sean; V. Seeman, Mary (Journal of Preventive Medicine And Care, 2016)
Background: Mental health promotion depends to a large extent on the gathering of accurate baseline opinion data from a targeted population. Aim: The aim of this paper is to explore the potential applications of a new method of measuring true attitudes toward mental illness, and of monitoring and evaluating subsequent public health interventions. Method: This paper reviews the strengths and limitations of a novel survey method, RIWI, its early findings, and its potential applications in the field of mental health promotion. Comparisons are made to other commonly used survey methods through entering pertinent search terms into the Google Scholar™ database. Findings: The RIWI online survey method has several advantages over earlier survey methods: it is random, quick, anonymous, and reaches very large samples. Questionnaires are easily translatable and can be repeated, with excellent test-retest reliability. Anonymity reduces social desirability bias. The limitations are: a) variable completion rate, which carries the upside of allowing regional comparisons, and b) the reality that the respondent pool reflects regional Internet usage, often biased toward young literate males. Conclusions: A survey method that is able to quickly and repeatedly sample large numbers of random individuals is an important advance for health promotion in that interventions can be timely and their efficacy can be rapidly evaluated.
Keywords: Mental Health Promotion; Survey Methodology; Prevention of Stigma